Distribution of Diagnoses and Clinical and Imaging Characteristics in 1,322 Consecutive Suspected Stroke Patients - Sporns, Peter B.; Brehm, Alex; Hilgers, Caroline; Ntoulias, Nikolaos; Tsogkas, Ioannis; Psychogios, Marios (Frontiers in Neurology, 2021)
Background: Endovascular thrombectomy (EVT) has become the standard of care for large-vessel occlusion strokes, but several barriers for implementing an optimal organization of stroke management remain. Major issues include the lack of reliable data on the percentage of stroke patients potentially eligible for EVT especially in times of expanding indications for EVT. Our aim was therefore to study the frequencies of possible EVT-eligible patients such as patients with medium-vessel occlusions, patients with low Alberta Stroke Program Early Computed Tomography Scores (ASPECTS), patients presenting in an extended time window after onset of symptoms, and patients with mild symptoms at presentation (National Institutes of Health Stroke Scale, NIHSS ≤ 5). We also give detailed imaging and clinical information about the patients presenting with intracranial hemorrhage and other ischemic stroke mimics stratified by symptoms at presentation. Methods: Cohort study of all consecutive patients with suspected acute stroke presenting to a tertiary care center in Germany between September 1, 2016, and August 31, 2017. Baseline and follow-up clinical and imaging characteristics were collected from patients' medical charts. Results: Of 1,322 patients with a suspected acute stroke, 592 (44.8%) had ischemic strokes, 221 (16.7%) had hemorrhagic strokes, 190 (10.9%) had transient ischemic attacks (TIAs), and 319 (24.1%) were classified as stroke mimics. Stroke severity was mild (NIHSS ≤ 5) in 866 (65.5%) patients; 15.7% of the patients with an occlusion of the anterior circulation had an ASPECTS ≤ 5, 17.4% of the patients with an ischemic stroke had distal vessel occlusions, and 49% of the patients presented later than 6 h after onset of symptoms. Conclusion: Our results help to plan resources in thrombectomy-capable centers in times of expanding indications for EVT where resources will have to be adjusted to patients with low-NIHSS, low-ASPECTS, and distal occlusions, and patients presenting in the extended time window, which may altogether account for an additional 20% of all ischemic stroke patients.